Green Chemistry: Effect of Microwave Irradiationon Synthesis of Chitosan for Biomedical Grade Applications of Biodegradable Materials - Amri Setyawati; Deni Pranowo; Indriana Kartini (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2016)
Microwave assisted chitosan synthesis as biodegradable material for biomedical application has been done. The purpose of this research is to synthesis of chitosan with high DD and low molecular weight using microwave energy, the study of reaction conditions include parameters of power and reaction time. Chitosan was prepared by deacetylation of chitin with 60% NaOH solution. Conventional method has been done by reflux for 90minutes, resulting chitosan with DD of 79.5%, 72.6% yields and molecular weight 6051 g/mol. Green chemistry method using microwave radiation at 800 Watts for 5 minutes has produced chitosan with highest DD, yield and molecular weight of 86%, 75% and 3797 g/mole respectively. Synthesis of Chitosan by microwave radiation method can save 10x electrical energy for the reaction, also rapidly and effectively to produce chitosan with low molecular weight compared to conventional methods